Recent Developments in the Field of 123I-Radiopharmaceuticals - Machulla, H.-J.; Knust, E. J. (Nuklearmedizin - NuclearMedicine, 1984)
Due to its advantageous nuclear physical properties iodine-123 is an excellent label for radiopharmaceuticals very well suited for measurements by γ-cameras and single-photon emission tomography. The development of 123I-radiopharmaceuticals should be based on a clear biochemical concept, reliable labelling procedures and careful pharmacokinetic studies in order to evaluate the physiological behaviour of the radioiodinated compounds being analogues of metabolic substrates. The development of 123I-labelled fatty acids and biogenic amines clearly proved the successful use of 123I for labelling compounds applied in medical diagnosis.